MENGEMBANGKAN BAHASA SIMBOLIK KREATIF UNTUK MENINGKATKAN KETERLIBATAN ORANG MUDA KATOLIK DALAM KATEKESE - Tjahaja, Liria (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
Catechesis must answer to the challengs of era in order to help people experience the presence of God in life which is increasingly complex. This article suggests the use of symbolic language which is creative as a contemporary approach in catechesis, especially for reaching the Catholic youth. Through the narative Catechesis model that has been renewed, researchers want to reveal that symbolic language can touch the inner hearts and as the some time to push the active participation of the youth. By utilising the digital development, this article offers an innovative strategy in preaching the faith teaching, applying the relevant way and interesting to the youth in this era.